The preferred genre between classical music and modern music among students in the Faculty of Music UiTM / Shammir Horace - Horace, Shammir (2014)
This study is to know about the preferred genre between classical music and modern music. The case study of this research is among music students in the faculty of music UiTM. The study also used to find out the background of the students that contributes to the choices of music. Next, this study will also investigate the problems face by students towards choosing the type of music that wanted to be played. Last but not least, this study also used to identify whether music career and job opportunities will influence the students' preferences in music. To achieve better results and understanding, this research is conducted in both quantitative and qualitative methods by using the questionnaire and interviewing few amateur and professional musicians. As a results, a lot of students wanted to change and switch their instrument to modem music which in UiTM described as Jazz music. By doing this research, we also can conclude that there are a lot of improvement can be made to improve our own music industry in Malaysia. It also help UiTM's students to plan properly and make good choices and learn to play and produce good music. As a recommendation, chances and encouragement should be given to students to choose and learn what music the wanted to learn. Teachers and lecturers could also plan wisely the process of learning and education that wanted to be teach to the students